Strategi Rekayasa Pengelolaan Kualitas Air di Sub DAS Tiku Musi Rawas Utara - Alfirmansyah Alfirmansyah; Insannul Kamil; Dwi Eri Yanti; Ummi Jayanti (Fakultas Teknik Universitas Cenderawasih, 2026)
This study aims to formulate an engineering strategy for water quality management and pollution control in the Tiku Sub-watershed, North Musi Rawas Regency. The study used a descriptive approach by integrating selected technical data from a dissertation-based assessment with semi-structured interviews involving 20 key informants representing technical agencies, village and subdistrict governments, community leaders, artisanal and small-scale gold mining actors, farmers, and riverbank communities. The analysis focused on water quality status, water availability and demand, pollution sources, perceived impacts, implementation constraints, and priority interventions. The results showed that the Tiku Sub-watershed is under significant environmental pressure. The average pollution index was 6.65, indicating a moderately polluted status, while mercury, cadmium, phosphate, and ammonia were the dominant parameters of concern. Surface water availability remained relatively adequate at 45,842,699.79 m3/year, and the average Criticality Ratio was 0.266; however, the water pollution carrying capacity was poor. Interview results indicated that mercury use and processing waste from artisanal gold mining were the most urgent issue (35%), followed by land-cover change and riparian degradation. The recommended strategy combines mercury-free processing technology, alternative livelihood development, cross-sectoral supervision, riparian rehabilitation, and transparent water-quality monitoring. The findings imply that watershed engineering should integrate technical, institutional, and socio-economic interventions.